DETERMINE THE MATERIAL INVENTORY FORECASTING METHOD BASED ON THE SMALLEST ERROR - Gunarti, Triana Sri; Tujni, Baibul; Solikin, Imam (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The research was conducted at TB Bina Karya which is engaged in the sale and purchase of building materials. This research was conducted to predict building materials for the next period. The forecasting methods used in this study are single moving average (SMA), weighted moving average (WMA), and single exponential smoothing (SES). This study also discusses the error calculation of the forecasting method, the forecasting method which produces the smallest error value is used for making decisions in purchasing materials. The purpose of this research is to speed up the decision making for purchasing material inventory. Another goal is to produce more accurate forecasts by comparing 3 (three) methods.            Keywords: forecasting; single moving average; weighted moving average; and single exponential smoothing  Abstrak: Penelitian dilakukan pada TB Bina Karya yang bergerak dibidang penjualan dan pembelian bahan material bangunan. Penelitian ini dilakukan untuk forecasting bahan material bangunan periode selanjutnya. Metode forecasting yang digunakan dalam penelitian ini yaitu single moving average (SMA), weighted moving average (WMA), dan single exponential smooting (SES). Penelitian ini juga membahasan perhitungan error dari metode forecasting, metode forecasting yang menghasilkan nilai error terkecil digunakan untuk pengambilan keputusan dalam pembelian bahan material. Tujuan dari penelitian ini untuk mempercepat dalam pengambilan keputusan pembelian persediaan bahan material. Tujuan lainnya adalah agar menghasilkan forecasting lebih akurat dengan membandingkan 3 (tiga) metode. Kata kunci: forecasting; rata-rata pergerakan tunggal; rata-rata pergerakan tertimbang; dan pemulusan eksponensial tunggal